Domestication technique of commercially important freshwater mud eel, Monopterus cuchia (Hamilton, 1822) - Jahan, Nusrat; Salam, Mohammad Abdus; Ahsan, Ali; Rahman, Mohammad Lutfar; Paul, Sulav Indra; Simon Kumar Das,; Mazumder, Sabuj Kanti (Penerbit Universiti Kebangsaan Malaysia, 2020)
The research was conducted to develop the domestication technique of Monopterus cuchia collected from Sherpur district, Bangladesh. A total of 300 young M. cuchia (average 95±6.4 g) was reared under nine treatments as earthen pond with dead fish (EpDf), earthen pond with live fish (EpLf), earthen pond with formulated feeds (EpFf), mud treated plastic tank with dead fish (PmDf), mud treated plastic tank with live fish (PmLf), mud treated plastic tank with formulated feeds (PmFf), plastic tank with dead fish (PtDf), plastic tank with live fish (PtLf), and plastic tank with formulated feeds (PtFf) with three replicates each. Size of each earthen pond was 1m3 and plastic circular tank was 0.322m3. Stocking density was maintained at 10 fish in each replicate by random selection. Survival, weight gain (WG), specific growth rate (SGR%/day), feed conversion ratio (FCR), feed conversion efficiency (FCE), and protein efficiency ratio (PER) were measured. The best survival (100±0), WG (61.17±1.83), SGR (0.118±0.026), FCR (2.44±0.17), FCE (35.75%±2.90), and PER (1.75±0.14) were obtained in EpLf, which was significantly higher (P<0.05) than others. This is the first report of domestication of M. cuchia and indicates that earthen pond with live fish might be suitable for domestication of M. cuchia.